Political Preferences Of Young Generation (Gen Y And Gen Z) Ahead Of The Contestation Of The 2024 West Java Governor And Vice Governor Elections - Wahyudy, Fahmy Iss (Universitas Tanjungpura, 2024)
Gen Y (millennials) and Z are predicted to have a vital role in the conduct of General Elections, this cannot be separated from quantitative data-based considerations, specifically their very large proportion of the total number of Voters. Within the context of the 2024 West Java Governor and Vice Governor Elections, such figure is realized to reach 54 percent. Given such background, it is not surprising that all components of interest, in this case the electoral committees, electoral candidates, and including academics are competing in making a more detailed map of the political preferences and voting behavior of gen Y and Z. This study uses a qualitative method and critical discourse analysis approach. This study seeks to show a number of factors in relation to the political preferences of gen Y and Z in the implementation of democratic mechanisms, specifically General Elections. These political preferences of gen Y and Z are mapped out through survey data, those survey data are analyzed in depth through the theory of voting behavior. This study is expected to be a reference for electoral committees and electoral candidates in the formulation of strategic policies to improve gen Y and Z's participation and involvement in electoral politics.